Correspondence between DOM molecules and microbial community in a subtropical coastal estuary on a spatiotemporal scale. (September 2021) - Chen, Qi; Chen, Feng; Gonsior, Michael; Li, Yunyun; Wang, Yu; He, Chen; Cai, Ruanhong; Xu, Jinxin; Wang, Yimeng; Xu, Dapeng; Sun, Jia; Zhang, Ting; et al.
Graphical abstract: Schematic of the coastal microorganism-mediated dissolved organic matter transformation. Highlights: Bacteria transformed the DOM from a relatively high to a low molecular weight. Microbial transformation render "dark" organic matter visible in mass spectrometry. K- and r-strategists showed different correlations with two-size categories of DOM. DOM chemodiversity and microbial biodiversity exhibited tight connections. DOM variations are more crucial in shaping microbial communities than vice versa. Abstract: Dissolved organic matter (DOM) changes in quantity and quality over time and space, especially in highly dynamic coastal estuaries. Bacterioplankton usually display seasonal and spatial variations in abundance and composition in the coastal regions, and influence the DOM pool via assimilation, transformation and release of organic molecules. The change in DOM can also affect the composition of bacterial community. However, little is known on the correspondence between DOM molecules and bacterial composition, particularly through a systematic field survey. In this study, the spatiotemporal signatures of microbial communities and DOM composition in the subtropical coastal estuary of Xiamen are investigated over one and half years. The co-occurrence analysis between bacteria and DOM suggested microorganisms likely transformed the DOM from a relatively high (>400 Da) to a low (<400 Da) molecular weight, corresponding to an apparent increase in overall aromaticity. This might be the reason why microbial transformation renders "dark" organic matter visible in mass spectrometry due to more efficient ionization of microbial metabolites, as well as photodegradation processes. K- and r-strategists exhibited different correlations with two-size categories of DOM molecules owing to their different lifestyles and responses to environmental nutrient conditions. A comparison of the environmental variables and DOM composition with the microbial communities showed that the environmental/DOM variations played a more important role in shaping the microbial communities than vice versa. This study sheds light on the interactions between microbial populations and DOM molecules at the spatiotemporal scale, improving our understanding of microbial roles in marine biogeochemical cycles.